Analysis of Spare Parts Inventory Control Using Economic Order Quantity (EOQ) Method at PT Astra International Tbk. Toyota Sales Operation AUTO2000 Bogor Siliwangi - Noorzaman, Sandi; Kartikasari, Maya Andini; Abdi, Muhammad Danawan Esa (Institut Ilmu Sosial dan Manajemen Stiami, 2023)
Along with the development of the current technological era is developing very quickly, one of which is land transportation, especially four-wheeled vehicles. From year to year vehicle technology is increasingly advanced so that it attracts people to have use for transportation or goods transportation purposes. However, along with its use, the vehicle needs regular maintenance so that it is always in prime condition and safe when driving. Therefore, companies engaged in vehicle maintenance and repair services need to prepare for the availability of spareparts to meet the needs of their customers. The type of research used is descriptive research. The data used in this study consists of primary data and secondary data that are qualitative in nature related to spareparts inventory. By using the EOQ method the company can save the total cost of inventory for tmo syn 10w-40sn 1lt around 85% or Rp. 2,652,961, tmo syn 10w-40sn 4lt about 89% or Rp. 2,774,200, element sa oil filter around 95% or Rp. 2,904,527, pad kit disc brake fr around 90% or Rp. 1,631,944 and 34b19r hybrid battery around 88% or Rp. 1,202,923.